Transcriptomics and metabolomics revealed that phosphate improves the cold tolerance of alfalfa - Wang, Yuntao; Sun, Zhen; Wang, Qiqi; Xie, Jihong; Yu, Linqing (Frontiers in Plant Science, 2023)
Alfalfa (Medicago sativa L.) is a highly nutritious leguminous forage that plays an essential role in animal husbandry. In the middle and high latitudes of the northern hemisphere, there are problems with its low rates of overwintering and production. The application of phosphate (P) is an important measure to improve the cold resistance and production of alfalfa, but little is known about the mechanism of P in improving the cold resistance of alfalfa. Therefore, this study integrated transcriptome and metabolome to explain the mechanism of alfalfa in response to low-temperature stress under two applications of P (50 and 200 mg kg-1) and a control of none applied. The results showed that the application of P fertilizer improved the root structure and increased the content of soluble sugar and soluble protein in the root crown. In addition, there were 49 differentially expressed genes (DEGs) with 23 upregulated and 24 metabolites with 12 upregulated when 50 mg kg-1 of P was applied. In contrast, there were 224 DEGs with 173 upregulated and 12 metabolites with 6 upregulated in the plants treated with 200 mg kg-1 of P compared with the CK. These genes and metabolites were significantly enriched in the biosynthesis of other secondary metabolites and the metabolic pathways of carbohydrates and amino acids. Integration of the transcriptome and metabolome indicated that P affected the biosynthesis of N-acetyl-L-phenylalanine, L-serine, lactose, and isocitrate during the period of increasing cold. It could also affect the expression of related genes that regulate cold tolerance in alfalfa. Our findings could contribute to a deeper understanding of the mechanism that alfalfa uses to tolerate cold and lay a theoretical foundation for breeding alfalfa that is highly efficient at utilizing phosphorus.